EFICIÊNCIA AGRONÔMICA DA AVEIA BRANCA NAS CONDIÇÕES DE FORNECIMENTO DE NITROGÊNIO - Oliveira, Juliana M. d.; Fuhrmann, Juliano W.; Antonow, Diovane; Mattini, Tânia C.; Arenhardt, Emílio G.; Schiavo, Jordana; Fontaniva, Cristiano; Matter, Edegar; Maixner, Adriano R.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo